P082 Evaluation of a new LGBTI service to complement a busy inner city GUM clinic. (30th June 2016) - Hamlyn, Eleanor; Cooney, Grainne; Randhawa, Kulvinder; Wood, Sue; Barber, Tristan
Abstract : Background/introduction: LGBTI individuals are at significantly increased risk of STI's and HIV, as well as sexual violence and discrimination. The need for specialist LGBTI services in level 3 GUM settings is increasingly recognised and also subscribes to BASHH equality and diversity standards. We established a new LGBTI specialist clinic and present here a service evaluation of its first 8 months. Aim(s)/objectives: To evaluate a new LGBTI service. Methods: Coding for all patients who accessed the service over an 8 month period was collated and used to garner basic information about diagnoses. A 4 week period was then chosen at random and individual patient notes were accessed to get more detailed information. Results: There were 526 attendances for 450 individual patients. The rates of STI's compared to our general clinics are tabled below. In the 4 week period there were 104 booked attendances. The age range was 19 – 75 (mean: 37.1). Of the 92 patients who attended 59% had at least one diagnosis with 13% having multiple diagnoses. 26% were HIV positive. Discussion/conclusion: The high STI and HIV rates in this group suggest they will benefit from a specialist service. This involves a reconfiguration of staff compared to general clinics to account for increased requirements for treatments, injections and counselling. An additional qualitative assessment demonstrated that the clinic was also extremely well received by patients.